Correlación de los resultados de impacto o tenacidad de 16 maderas mexicanas utilizando dos métodos de prueba - Bárcenas Pazos, Guadalupe; Zárate Morales, Reyna Paula; Ordóñez Candelaria, Víctor Rubén; Guerrero Báez, Abigail; Honorato Salazar, J. Amador (Instituto de Ecología, A.C., 2016)
The wood impact bending resistance is considered an important mechanical property, mainly to determine the suitability of woods to be used for tool hammers or sport goods, such as pistol handles, base ball bats and other uses where it would be a need to absorb and to disperse energy during impact. There are several test methods to determine wood shock resistance, among those used in Mexico are the toughness test based on the ASTM D143  standard (ASTM, 1999) and the Impact or dynamic flexure test, based on the NF B51-009 standard (AFN, 1942). Each method produces values in different units. In order to find the correlation between the results from these two different test method to allow the comparison and homogenization of data already published on Mexican woods impact bending resistance, a testing program for 16 woods was carried out. Test were performed in green and dry conditions in both testing methods. An equation from a simple regression linear analysis was obtained comparing both sets of results. The equation will help to wide the scope of the knowledge on mechanical properties of Mexican woods.